Standardization and quality evaluation of Cassia surattensis seed extract - Saravanan, A Dharmaraj; Seeta, Uthaya Kumar; Subramanion L, Jothy (2014)
Standardization and quality control of herbal products used for the development of medicinal materials is important. The objective of the present study is to standardize the Cassia surattensis seed extract. Various chromatographic and spectral fingerprinting techniques, and heavy metal analysis and microscopy of seed were used to standardize the C. surattensis seed. The findings of the current study can be useful to progress and surge further scientific investigation on the seeds of this species. Pharmacognostic investigation of the fresh and anatomical sections of the seeds of C. surattensis was carried out. Pharmacognostic evaluation confirmed the authenticity of the seeds which involved parameters like gross morphology, microscopy of the seeds and functional group analysis by Fourier Transform Infrared (FTIR) spec troscopy. The chromatographic and spectroscopic evaluation provided the qualitative and semi quantitative information about the main active constituents present in the seed extract. The concentrations of heavy metals determined in the C. surattensis seed extract were well below the permissible limit. Standardization of C. surattensis is needed to ensure their safe and quality control for effective use.